SOSIALISASI PERILAKU HIDUP BERSIH DAN SEHAT ( PHBS ) DENGAN SISTEM TIGA JEMPOL PADA SISWA SDN 016 ANTASARI KOTA SAMARINDA - Naheria Naheria; Nurjamal Nurjamal; Didik Cahyono; Muhammad Sukron Fauzi; Gyta Krisdiana (Pusat Riset dan Inovasi Nasional, 2022)
The health profile book for the province of East Kalimantan in 2016 Sickness Rate (Morbidity) describes the incidence of disease in a population over a certain period of time, which can be in the form of incidence rates or prevalence rates of a disease. The morbidity rate also plays a role in assessing the health status of the community. Data on population morbidity comes from the community (community based data) obtained through a morbidity study, and the results of data collection from the District/City Health Office, the health program manager at the provincial level. The morbidity rate in 2013 was 11.74 and decreased in 2014 to 9.18 and increased in 2016 to 11.90. (Dinkes: 2016) The implementation of PHBS is low, because there are still many students who eat snacks carelessly and there is still garbage scattered in the school yard. The UKS exists but the program does not run due to the lack of supporting facilities, and their lack of knowledge regarding how to wash hands properly and correctly. Aims to increase the knowledge of elementary school students in clean and healthy living behavior through the Socialization of Clean and Healthy Life Behavior (PHBS) with the Three Thumb system, Provide understanding and awareness to elementary school students about the importance of the school PHBS program Able to reduce morbidity due to lack personal hygiene in the school environment. The method used in this activity is the lecture method, demonstration method and practical method, data collection techniques, namely the initial test and the final test. The result is that there is an increase of 21% of students' knowledge of the importance of PHBS.